Investigating the association of chemokine receptor 5 (CCR5) polymorphism with cervical cancer in human papillomavirus (HPV) positive patients - DOI: 10.4025/actascihealthsci.v30i2.944 (Acta Scientiarum. Health Sciences, 2008)
HPV is one of the most frequent causes for the development of cervical cancer. It is known that chemokines are important determinants of early inflammatory responses. The CC chemokine receptor 5 (CCR5) gene is involved in the chemotaxis of leukocytes toward inflammation sites. In the present study, polymerase chain reactions (PCR) in genomic DNA samples, using specific CCR5 oligonucleotide primers surrounding the breakpoint deletion, detected a 225 bp product from the normal CCR5 allele and a 193 bp product from the 32 bp deletion allele. The wild type genotype was prevalent in both group, but it was not statistically significant, with Ï‡2 = 1.519 (2 degrees of freedom; p > 0.05). As there are a small number of ï„32 allele carriers, further studies are needed to clarify the role of CCR5 in the cervical cancer.